"So that's why I'm scared of these methods": Locating contraceptive side effects in embodied life circumstances in Burundi and eastern Democratic Republic of the Congo. (January 2019) - Schwarz, Joëlle; Dumbaugh, Mari; Bapolisi, Wyvine; Ndorere, Marie Souavis; Mwamini, Marie-Chantale; Bisimwa, Ghislain; Merten, Sonja
Abstract: Contraceptive side effects (SE) are often portrayed as either unproblematic trade-offs for pregnancy prevention or misconceptions and fears that negatively affect individuals' contraceptive decisions. Little attention is given, however, to wider, socially-rooted meanings and rationales for these feared and experienced SE. Through inductive analysis of in-depth interviews conducted with women and men from rural Burundi and South Kivu province, Democratic Republic of the Congo between 2013 and 2016, we locate contraceptive SE narratives in individuals' broader and changing life circumstances. We extracted two conceptual categories related to SE from participants' narratives: 1) bodily symptoms attributed to modern contraception; and 2) social meanings of SE in everyday life. We then situate these narratives in context – sources of knowledge on SE, barriers to addressing SE, and individuals/couples' life circumstances – to understand their embodied realities. Using Krieger's ecosocial theory, our findings suggest that in rural contexts of poverty, uncertainty and power inequities the empirical realities of SE are legitimate concerns stemming from actual or anticipated bodily symptoms located in the embodied life circumstances of individuals and couples. Highlights: Unique inductive analysis of contraceptive side effect narratives from central Africa. Embeds contraceptive side effects and social meaning in fragile contexts. Legitimizes local populations' concerns with biomedical contraceptive side effects. Argues for definitive shift in dominant international family planning discourse.